Poverty Forecasting Analysis in Bengkulu Province in 2025-2027 - Situngkir, Kartika Yuni Hartati; Barika, Barika (Formosa Journal of Multidisciplinary Research, 2024)
Poverty remains a major challenge in Bengkulu Province, with a relatively high poverty rate compared to other provinces in Sumatra. This study aims to predict the poverty rate in Bengkulu Province using the Markov Chain approach for the period 2025-2027, based on historical data from 2015-2024 obtained from the Central Statistics Agency (BPS). Through the analysis of transition probabilities between poverty statuses using the Markov Chain approach, this study found that most districts/cities in Bengkulu Province showed a consistent downward trend in poverty, especially in areas such as South Bengkulu and Rejang Lebong. However, several areas, such as Central Bengkulu and Seluma, still experience quite high poverty rates, and are even predicted to increase in the coming years. This indicates that these areas require more attention in poverty alleviation policies. The results of this prediction are expected to be a reference for the government in formulating more effective poverty alleviation policies, with a focus on increasing access to education, health, and job creation. Thus, this study provides an important contribution to more targeted policy planning to reduce poverty levels in Bengkulu Province.